Human physiology in extreme environments - Gunga, Hanns-Christian; Opatz, Oliver; Steinach, Mathias; Stahn, Alexander Christoph (Amsterdam : Academic Press, 2015)
Human Physiology in Extreme Environments is the one publication that offers how human biology and physiology is affected by extreme environments while highlighting technological innovations that allow us to adapt and regulate environments. Covering a broad range of extreme environments, including high altitude, underwater, tropical climates, and desert and arctic climates as well as space travel, this book will include case studies for practical application. Graduate students, medical students and researchers will find Human Physiology in Extreme Environments an interesting, informative and useful resource for human physiology, environmental physiology and medical studies.
Online resource; title from PDF title page (Ebsco, viewed Jan. 14, 2015).
Includes bibliographical references and index.
Keywords: Extreme environments -- Physiological effect; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Extreme environments -- Physiological effect; Electronic books